2010
DOI: 10.1186/1471-2164-11-556
|View full text |Cite
|
Sign up to set email alerts
|

Response of swine spleen to Streptococcus suis infection revealed by transcription analysis

Abstract: AstractBackgroundStreptococcus suis serotype 2 (SS2), a major swine pathogen and an emerging zoonotic agent, has greatly challenged global public health. Systematical information about host immune response to the infection is important for understanding the molecular mechanism of diseases.Results104 and 129 unique genes were significantly up-regulated and down-regulated in the spleens of pigs infected with SS2 (WT). The up-regulated genes were principally related to immune response, such as genes involved in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 79 publications
(100 reference statements)
2
35
0
Order By: Relevance
“…suis infection-induced TREM-1 expression and high serum proinflammatory cytokine levels in a mouse model. Our previous transcription analysis indicated that TREM-1 expression was upregulated in the pig spleen and that some genes encoding proinflammatory cytokines were also upregulated during S. suis infection (41). The present mouse infection study also indicates that S. suis infection can induce trem-1 transcription (Fig.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…suis infection-induced TREM-1 expression and high serum proinflammatory cytokine levels in a mouse model. Our previous transcription analysis indicated that TREM-1 expression was upregulated in the pig spleen and that some genes encoding proinflammatory cytokines were also upregulated during S. suis infection (41). The present mouse infection study also indicates that S. suis infection can induce trem-1 transcription (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Our previous transcription analysis of the swine response to S. suis infection indicated that the gene encoding TREM-1 was upregulated and that a few inflammatory-response genes were also highly expressed (41). Given the role of TREM-1 signaling in the enhanced proinflammatory response associated with the pathogenesis of S. suis, we examined the effect of TREM-1 signaling on the outcome of S. suis infection.…”
mentioning
confidence: 99%
“…S1) . In contrast to pathogenic SS2, Δ hp0197 infection did not induce high levels of cytokine expression [63], which could be provoked by highly pathogenic SS2 [55], [63], [64]. These data indicated that hp0197 significantly contributed to S. suis virulence.…”
Section: Discussionmentioning
confidence: 77%
“…Within S. aureus abscesses, manganese and zinc levels are very low due to increased production of the metal binding host protein calprotectin (14). Interestingly, a recent transcriptome study of swine spleen showed a strong upregulation of calprotectin (also named S100A8/S100A9) after S. suis challenge (25). Our observations of reduced disease and mortality and of reduced bacterial recovery from organs of ⌬troA mutant-infected mice strongly suggest that TroA is an important virulence factor and contributes to overcome nutritional immunity of the host.…”
Section: Discussionmentioning
confidence: 99%